Improving Cooperation and Critical Thinking Ability Using The "Be Smart" Model in Primary School Students - Nisa Yunita; Celia Cinantya (Journal of Elementary School Education, 2024)
The problem in this research is the low level of cooperation and critical thinking abilities of students. The reason is that learning is one-way and the use of inappropriate learning models to stimulate critical thinking. An effort to overcome this is by using the "BE SMART" model. The purpose of this research is to analyze the increase in students' cooperation and critical thinking abilities. This research is Classroom Action Research (PTK) which was carried out in four meetings. The research subjects were 22 class V students at SDN Mawar 7 Banjarmasin. The type of research used is qualitative and quantitative data. The results of the research showed that student cooperation in meeting I was 45%, increasing in meeting IV by 95% in the category "All Students Work Together". Students' critical thinking abilities at meeting I were 41%, increasing at meeting IV at 95% in the category "All Students are Critical". It is recommended to teachers that the results of this " BE SMART " model research can be used as a reference in using innovative learning models.